Development of Cursive Writing Learning Textbooks for Lower-Grade Elementary School Students - Harun Arasyid; Ani Widosari; Mukti Amini (Pedagogik Journal of Islamic Elementary School, 2022)
This study aims to produce cursive writing skills learning textbook for lower-grade students in elementary school that is valid, practical, and effective. This type of research uses research and development with a borg and gall design. This study will focus on improving the cursive writing skills of lower-grade students in four elementary schools in the Karanganyar sub-district. Researchers collect data using observation techniques, interviews, questionnaires, and tests to determine the needs of teachers and students and determine the quality of the products that have been developed. The collected data were then analyzed using qualitative descriptive and statistical analysis techniques. The results of the statistical analysis were converted into qualitative values. The data on the cursive writing skills test results will go through N-gain, normality, and homogeneity. The results of this study indicate that the product developed gets a proper category based on the validation of experts and the responses of students and teachers. There is an increase in students' cursive writing skills after using soft writing learning textbooks.